Using Caco-2 cells as novel identification tool for food-derived DPP-IV inhibitors. (February 2017) - Caron, Juliette; Domenger, Dorothée; Dhulster, Pascal; Ravallec, Rozenn; Cudennec, Benoit
Abstract: Dietary proteins have recently been investigated as a new source of DPP-IV inhibitory peptides with limited side effects and promising applications. Numerous studies have highlighted and identified peptide sequences able to inhibit DPP-IV activity in vitro, mostly from milk proteins. However, the correlation to in vivo studies remains scarce because standard in vitro assays with purified enzyme do not accurately simulate key factors impacting peptide bioactivity such as intestinal and brush border enzymes or cellular permeability. Therefore, a DPP-IV activity inhibition assay is here proposed using non differentiated confluent Caco-2 cells to rapidly assess food-derived peptide inhibitory potential in approaching intestinal conditions. DPP-IV gene expression was first checked and specific DPP-IV substrate was used to implement the assay. Using a specific DPP-IV inhibitor confirmed that non differentiated Caco-2 cells express measurable DPPIV activity. This in situ assay was then applied to digests which already demonstrated a DPP-IV inhibitory potential with a standard assay using purified enzyme. Bovine hemoglobin and cuttlefish hydrolysate digests from simulated gastrointestinal digestion exerted a dose response inhibition on DPP-IV activity but displayed different inhibitory potentials. Graphical abstract: Highlights: Dietary proteins have gained considerable attention as sources of DPP-IV inhibitors. Classic in vitro assays do not simulate parameters that compromise bioactivity. Caco-2 cells are a reliable model of intestinal epithelial cells and express DPP-IV. Here we described a new tool for DPP-IV inhibitors screening using living cells.